Sistema progresivo penitenciario en Colombia: tratamiento y resocialización (2020)
The objective of this study is to explore the progressive penitentiary system in Colombia, taking into account the stipulations of articles 142, 143, and 144 of Law 65 of 1993. In view of this context, this article examines whether the progressive system, introduced into criminal legislation on 1936, has been effective, or whether it should be reconsidered. The research methodology is documentary and aims, by means of consulting the doctrines, jurisprudence, norms, and reports of the inpec, to collect information relative to this topic which underpins the research in order to make an approximation analysis to the subject matter and conclude on its ineffectiveness. Among the findings, it failure stands out.